What is the mechanism of paroxysmal atrioventricular block in a patient with recurrent syncope?. Issue 6 (27th September 2019) - Bansal, Raghav; Mahajan, Ankit; Rathi, Chetan; Mehta, Akshay; Lokhandwala, Yash
Abstract : Paroxysmal atrioventricular (AV) block is characterized by sudden appearance of complete heart block with no escape rhythm. Three types have been described having different mechanisms namely, vagally mediated, intrinsic, and idiopathic. A rare case scenario is being described with the occurrence of paroxysmal AV block of all three types in the same patient.